THE IMPACT OF COSTUMER BASED BRAND EQUITY TOWARD REPURCHASE INTENTION OF GARUDA INDONESIA IN PONTIANAK WITH BRAND PREFERENCES AS MEDIATING VARIABLE - admin, Muhammad Ebuziyya Alif Ramadhan B12111016 (Jurnal Manajemen Update, 2017)
The aims of this research are (1) to analyze the effect of Garuda Indonesia Airline service’s customer-based brand equity toward brand preference of customers in Pontianak. (2) To observe the influence of brand preference toward repurchase intention of Garuda Indonesia Airline customers in Pontianak. (3) This research also aims to test the effect of customer-based brand equity toward repurchase intention of Garuda Indonesia’s customers. Independent variable in this research is customer-based brand equity, while repurchase intention acts as dependent variable, the intervening variable of this research is brand preference which its role is whether strengthen or weaken the effect of customer-based brand equity toward repurchase Intention. Research’s population is experienced costumers who have been served by Garuda Indonesia and also potential customers from the stated airline. The respondent is limited by minimal age group which is 18 years old minimum. The technique the writer used in this research is purposive sampling with 100 people as the respondents. Causality research is chosen as the form of the research. Data Analysis technique that writer used is multiple linear regression method or path analysis. Research’s result shows that customer-based brand equity affects positive and significantly toward brand preference of Garuda Indonesia airline’s service, brand preference shows positive and significant result toward repurchase intention of the service and lastly, customer-based brand equity also shows positive and significant effect toward repurchase intention of Garuda Indonesia Airline service.